2020
DOI: 10.1186/s13063-020-04568-9
|View full text |Cite
|
Sign up to set email alerts
|

Expression levels of circulating miRNAs as biomarkers during multimodal treatment of rectal cancer - TiMiSNAR-mirna: a substudy of the TiMiSNAR Trial (NCT03962088)

Abstract: Background: Neoadjuvant chemoradiotherapy followed by surgery is the mainstay treatment for locally advanced rectal cancer, leading to significant decrease in tumor size (downsizing) and a shift towards earlier disease stage (downstaging). Extensive histopathological work-up of the tumor specimen after surgery including tumor regression grading and lymph node status helped to visualize individual tumor sensitivity to chemoradiotherapy, retrospectively. As the response to neoadjuvant chemoradiotherapy is hetero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…ncRNAs may represent suitable surrogate biomarkers. To date, some molecular diagnostic and predictive panels of ncRNAs are available, for example, OsteomiR (TAmiRNA) for osteoporosis, ThrombomiR (TAmiRNA) for cardiovascular diseases, ThyraMIR and ThyGENX (Interpace Diagnostics/Asurgene) for thyroid and pancreatic cancer, miRview Mets (Roseta genomics/Precision Therapeutics) to identify the origin of cancer, Reveal (Genoptix) for Thyroid cancer, and even more in clinical trials (Monsellato et al, 2020; Weigl et al, 2021). The primary research is focused on miRNAs; however, other epigenetic factors are also promising (Bonneau et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…ncRNAs may represent suitable surrogate biomarkers. To date, some molecular diagnostic and predictive panels of ncRNAs are available, for example, OsteomiR (TAmiRNA) for osteoporosis, ThrombomiR (TAmiRNA) for cardiovascular diseases, ThyraMIR and ThyGENX (Interpace Diagnostics/Asurgene) for thyroid and pancreatic cancer, miRview Mets (Roseta genomics/Precision Therapeutics) to identify the origin of cancer, Reveal (Genoptix) for Thyroid cancer, and even more in clinical trials (Monsellato et al, 2020; Weigl et al, 2021). The primary research is focused on miRNAs; however, other epigenetic factors are also promising (Bonneau et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…And they are usually elevated in patients with cancers. 9 During chemotherapy, CEA and CA19-9 usually change dynamically. 10 Previous studies have shown CEA and CA19-9 have good diagnostic and prognostic value in gastric, breast and colorectal cancers.…”
Section: Introductionmentioning
confidence: 99%
“…10 Previous studies have shown CEA and CA19-9 have good diagnostic and prognostic value in gastric, breast and colorectal cancers. [9][10][11] However, these studies were either limited to CEA and CA19-9 changes after chemotherapy instead of after NCRT or focused on stage IV RC instead of stage II/III. 12,13 Moreover, previous research only evaluated the prognostic value of single tumor biomarker changes, instead of combining them.…”
Section: Introductionmentioning
confidence: 99%